Hypoid gear vehicle axle efficiency - Kakavas,I; Olver,AV; Dini,D (Tribology International, 2016)
In this paper, a study of a hypoid gear vehicle axle is presented. Using a custom rig, load-independent losses have been accurately measured and the effect of viscosity on spin loss has been quantified. Solution methods for the calculation of component losses are presented and combined into a complete thermally coupled transient model for the estimation of axle efficiency. An analysis of hypoid gear kinematics reveals a simplification, commonly adopted by other researchers, regarding the velocity of the point of contact in hypoid gears, to be in error. As a result, the calculation of lubrication parameters has been improved. Finally, experimental measurements are compared to the generated simulation results for a number of operating scenarios and satisfactory correlation is observed.